2018
DOI: 10.17554/j.issn.2311-5106.2018.05.269
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Gunshot Wounds of the Upper Extremity

Abstract: BACKGROUND: Gunshot wounds to the upper extremity in pediatric patients are an uncommon injury, but their impact on the patient can be severe. They can be accompanied by nerve damage, bone fracture, or tendon rupture. The most common cause of these pediatric gun injuries is unintentional firearm discharge. The most common type of firearm involved overall is a powdered weapon; however, non-powder weapons are a significant contributor to pediatric firearm injury. The purpose of this study is to describe the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In this study, we found that half the study population underwent a major surgical procedure, which supports the existing literature [18]. This is the first study on a national level to describe the specific procedures performed on children and young adults with nonpowder weapon injuries, with prior work having focused on specific injuries or body parts rather than all injuries and all procedures [2,3,19]. While the majority of procedures were relatively low acuity or complexity, a concerning number of children required significant surgical intervention.…”
Section: Procedures Associated With Nonpowder Weaponssupporting
confidence: 82%
“…In this study, we found that half the study population underwent a major surgical procedure, which supports the existing literature [18]. This is the first study on a national level to describe the specific procedures performed on children and young adults with nonpowder weapon injuries, with prior work having focused on specific injuries or body parts rather than all injuries and all procedures [2,3,19]. While the majority of procedures were relatively low acuity or complexity, a concerning number of children required significant surgical intervention.…”
Section: Procedures Associated With Nonpowder Weaponssupporting
confidence: 82%
“…1 Of those injured, 19,583 (38%) had an injury to their extremity. 5,7,[9][10][11][12][13][15][16][17][18][19][20][21][22][23][24]26 The lower extremity was more often involved than the upper extremity (51%). 6,11,13,15,17,[19][20][21]23,24,26 Handguns were involved in 76% of the incidents, followed by shotguns (11%), non-powdered weapons (7%), and rifles (2%) (Figure 2).…”
Section: Demographic Informationmentioning
confidence: 99%
“…6,11,13,15,17,[19][20][21]23,24,26 Handguns were involved in 76% of the incidents, followed by shotguns (11%), non-powdered weapons (7%), and rifles (2%) (Figure 2). [7][8][9][10][11][13][14][15]17,[20][21][22][23] Most of • Children with gun injuries involving the physis should be followed for growth arrests and those with retained bullet fragments close to bone or joints for lead toxicity. the victims were assaulted (63%) or a target for violence, whereas 33% were accidental, 3% were suicide attempts, and 1% were due to law enforcement.…”
Section: Demographic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This presents an etiology of significant morbidity in both adult and pediatric populations. 3 Optimal treatment consists of debridement, antibiotics, reconstruction, and rehabilitation. 2 Among patients requiring surgery, those presenting with simultaneous bone and joint defects provide a unique reconstructive challenge.…”
mentioning
confidence: 99%